Is It True That Transformational Leadership Style Can Shape Employees Motivation and Performance? - Hafid Kholidi Hadi (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2018)
Today the world is experiencing very rapid progress in all aspects of life. Along with these advances, strong human resources with good the quality are increasingly needed to face the rapid and continuous change. Limited Liability Company (Perseroan Terbatas/PT) is a profit-oriented business entity. PT. Berau Karya Indah is a new PT in raw material processing industry which is trying to develop production in the manufacturing sector. This study aims to discuss and analyze the influence of transformational leadership style on employees performance and motivation in PT. Berau Karya Indah Surabaya. The population used in this study is all 340 employees of the company. Sample size in this study included 172 respondents who were selected using random sampling technique. The result of this research indicates that transformational leadership style has a significant influence on employee performance and transformational leadership has a significant impact on employees work motivation.